Path Analysis on Life Course Factors Affecting Overweight and Obesity in Children Aged 2 to 5 Years Old in Surakarta - Uyunun Nudhira; Cri SP Wekadigunawan; Bhisma Murti (Masters Program in Public Health, 2017)
Background: Globally, prevalence of obesity in children under 5 years old has been increasing from 32 million in 1990 to 42 million in 2014. Indonesia ranks highest in the number of obesity cases in South East Asia with prevalence of 11.5% in 2013. However, child overweight and obesity have not been the focus of health problems in Indonesia. Early intervention and prevention of child obesity can reduce long-term risk of chronic diseases in adulthood. This study aimed to analyze the life course factors affecting overweight and obesity in children aged 2 to 5 years old in Surakarta.Subjects and Method: This was an analytic observational study with case control design. The study was conducted in 5 community health centers, Surakarta, from September to October, 2017. A total sample of 150 children aged 2 to 5 years old was selected using fixed disease sampling. The dependent variable was overweight or obesity. The independent variables were nutrition intake, exclusive breastfeeding, starting age of complementary feeding, physical activity, birthweight, age of gestation, sectio cesarea labor, maternal body mass index, and maternal job. Physical activity data was measured using Pre PAQ questionnaire. Other data were collected using a set of questionnaire and maternal and child health monitoring book. The data were analyzed by path analysis.Results: Overweight and obesity in children aged 2 to 5 years old were positively affected by over nutrition intake (b= 1.9; 95% CI= 0.15 to 3.60; p=0.033), high maternal body mass index (b= 2.0; 95% CI= 0.51 to 3.42; p=0.008), and sectio cesarean birth (b= 2.1; 95% CI= 0.56 to 3.73; p=0.008). Overweight and obesity in children aged 2 to 5 years old were negatively affected by normal birthweight (b= -2.2; 95% CI= -4.28 to -0.19; p=0.032), exclusive breastfeeding (b= -2.0; 95% CI= -3.60 to -0.39; p=0.015), timely starting age of complementary feeding (b= -1.3; 95% CI= -2.80 to 0.11; p=0.072), and high physical activity (b= -3.0; 95% CI= -4.63 to -1.37; p=0.001). Birthweight was positively affected by age of gestation (b= 4.2; 95% CI= 1.99 to 6.32; p=0.001) and was negatively affected by maternal body mass index (b= -1.1; 95% CI= -2.11 to -0.13; p=0.025). Exclusive breastfeeding was negatively affected by working outside the house (b= -1.4; 95% CI= -2.10 to -0.72; p= 0.001).Conclusion: Overweight and obesity in children aged 2 to 5 years old are positively affected by over nutrition intake, high maternal body mass index, and sectio cesarean birth. Overweight and obesity in children aged 2 to 5 years old are negatively affected by normal birthweight, exclusive breastfeeding, timely starting age of complementary feeding, and high physical activity.Keyword: life course factors, overweight, obesity, path analysis.Correspondence: Uyunun Nudhira. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: uyununnudhira14@gmail.com. Mobile: +6285253781714Journal of Epidemiology and Public Health (2017), 2(3): 267-283https://doi.org/10.26911/jepublichealth.2017.02.03.08